G-Site development as Teaching Materials and Science Learning Media to Improve Junior High School Student Learning Outcomes on Plant Structure materials - Arif Hadi Broto; Mieke Miarsyah; Rizhal Hendi Ristanto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Natural science learning during the Covid-19 pandemic has quite a high challenge because students and teachers cannot learn directly. Knowing the effectiveness of using Google-site as a material and media for student learning during distance learning to improve student learning outcomes is the aim of this study. This research was conducted at SMP PGRI 1 Karang Tengah Tangerang in grade 8. Purposive sampling was carried out for sampling in this study, so that class 8-E was the experimental class and class 8-E was the control class. The results showed that the use of Google-site as teaching materials and learning media was feasible. The use of Google-site as teaching materials and learning media has no significant effect seen from the Mann Whitney test of 0.419. The average N-gain test obtained from the control class was 0.029, while the experimental class was 0.051. The comparison of the mean value of the control class pretest and posttest was 1.4 points, while the average score of the ecaperimen class was 3 points. Based on this, it can be concluded that the use of Google-site as a material and media for student learning during distance learning can be used to improve student learning outcomes. However, several revisions are needed so that teaching materials and media are more effective in improving student learning outcomes independently.